Postoperative infection following anterior cervical fusion surgery caused by Prevotella oris: a case report - Wang, Chenglong; Lei, Yang (Frontiers in Surgery, 2025)
Postoperative infections following spinal fusion procedures are commonly caused by pathogens such as Staphylococcus aureus, coagulase-negative Staphylococcus, Streptococcus species, and Escherichia coli. However, cases involving Prevotella oris as a causative agent are rarely documented in the literature. We report a case of postoperative infection after anterior cervical spinal fusion surgery. After empirical antimicrobial therapy failed, high-throughput nucleic acid sequencing detected Prevotella oris in the patient's cerebrospinal fluid—a rare and previously unreported finding. Upon switching to a more sensitive antibiotic regimen, the patient's symptoms improved significantly. This case highlights an unusual etiology and provides a comprehensive documentation of the treatment process, aiming to assist clinicians in the diagnosis and management of similar infections.